Prevalence and factors associated with intermediate and high probability of pulmonary hypertension based on echocardiography of patients with systemic lupus erythematosus attending Rheumatology Clinical Hospital Selayang / Nur Farhana Abd Manaf ... [et al.] - Abd Manaf, Nur Farhana (2019)
Introduction: Pulmonary hypertension (PH) in SLE has a wide prevalence with significant morbidity and mortality if not detected early. This study aims to determine the prevalence of intermediate and high probability of pulmonary hypertension (PH) in SLE patients, to investigate its associated factors and to determine the relationship on between NT-proBNP, 6minute walk test and echocardiography findings. Method: This is a cross-sectional study involving SLE patients who were followed-up in a Malaysian rheumatology centre. A total of 60 patients underwent echocardiogram, 6-minute walk test and NT-proBNP test. Probability of pulmonary hypertension was determined based on ESC guideline. The demographic characteristics, SLE clinical manifestation and immunological profile, 6-minute walk test, echocardiography features and NT-proBNP were compared between groups of low, and intermediate and high probability of PH. Correlations of NT-proBNP, 6-minute walk test and echocardiogram ‘PH signs’ were analysed. The parameters of 6-minute walk test and achicardiogram ‘PH signs’ were compared between groups of low and high NT-proBNP levels were also analysed, with a cut-off of 150 Results: The prevalence of intermediate and high probability of PH in SLE patients was 16.7%. We did not find significant associated factors with intermediate and high PH probability, apart from oxygen saturation post 6-minute walk test. Patients with elevated level of NT-proBNP level had significantly shorter 6-minute walk distance (340.91±43.69m, p=0.009) and higher TRVmax (2.83±0.74 m/s, p=0.006), PRVmax (1.82±0.71 m/s, p=0.004), PA diameter (24.27±2.284m, p=<0.001) and IVC size (16.09±3.30mm, p=0.002) compared to those with low NT-proBNP level. Conclusion: This study found a high prevalence (16.7%) of SLE-PH according to echocardiography finding. We found that patients with intermediate and high PH probability had significantly lower oxygen saturation post 6-minute walk test and since this is an easy and cheap test, this can be an initial test to be performed on all SLE patients. We have shown NTproBNP had significant relationship with distance in6-minute walk test and PH signs in ECHO. It is therefore, a useful test to be considered for initial SLE-PH assessment, especially in patients who are not able to perform a 6-minute walk test.